Observing Teacher’s Motivational Teaching Practices in an EFL Class during Covid 19 Pandemic - Rizki Farani; Qowiyun Ma’rufah (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
Covid 19 pandemic breakout is a sudden wake up call for educators in terms of elevating the quality of EFL online learning activities. Several previous studies have proven that students’ motivation is one of the important aspects in learning English. However, each educator has different teaching practices. There is no standard on how teachers design strategies to motivate their students. Therefore, it is essential to explore various kinds of teachers’ techniques in motivating students. To reveal more motivational techniques in EFL settings, this study aims to observe teacher’s motivational teaching practices in one of Senior High Schools in Yogyakarta. By using qualitative method in a form of an observational study, this research captured online learning activities in an English subject online classroom. The data was collected by using observational checklist and field notes. As additional data, interview was conducted as confirmatory data. An English teacher volunteered herself to be the participant who explained about motivational teaching practices. After collecting data through video recording, LMS activities and interview, the data was analysed by using thematic analysis technique based on motivational teaching practice’s components. The results show that teachers mostly use positive retrospective self-evaluation by providing feedbacks and reward. In addition, teacher also generated initial motivation by maintaining and protecting students’ motivation during learning. In sum, teacher has succeeded to create basic motivational condition. It implies that student-teacher interaction in online learning is not only limited to share materials and conduct assessment but also build positive and safe environment for students.